Genome-scale molecular and phylogenetic characterization of Middle Point orbiviruses from Australia. (6th December 2021) - Agnihotri, Kalpana; Oakey, Jane; Smith, Craig; Weir, Richard; Pyke, Alyssa; Melville, Lorna
Abstract : Middle Point orbivirus (MPOV) is an Australian arbovirus, belongs to the Yunnan orbivirus species found in China. First detected and reported from Beatrice Hill, Northern Territory (NT), MPOV has to date, only been exclusively reported from the NT, Australia. Whilst genetic characterization of MPOV has been previously described, only restricted to sequence information for segments 2 and 3 coding core protein VP2 and outer capsid protein VP3, respectively. This study presents for the first time nearly full-length genome sequences of MPOV, which represent 24 isolates collected over a span of more than 20 years from 1997 to 2018. Whilst the majority of isolates were sampled at Beatrice Hill, NT where MPOV is most frequently isolated, this report also describes the first two isolations of MPOV from Queensland (QLD), Australia. One of which is the first non-bovine isolate obtained from the mosquito vector Aedes vittiger . We further compared these MPOV sequences with known sequences of the Yunnan orbivirus and other known orbivirus sequences of mosquito origin found in Australia. The phylogenetic analyses indicate the Australian MPOV sequences are more closely related to each other than other known sequences of Yunnan orbivirus. Furthermore, MPOV sequences are closely related to sequences from the Indonesian isolate JKT-8650. The clustering of Australian sequences in the phylogenetic tree suggests the monophyletic lineage of MPOV circulating in Australia. Further, ongoing surveillance is required to assess the existence and prevalence of this or other yet undetected lineages of MPOV and other orbiviruses in Australia.